(untitled) (Medico Legal Update, 2020)
Background: Nurses’ adherence to ethical values in the field of patient care is affected by various factors, especially moral intelligence. The role of moral intelligence on professional commitment is an issue leading to improving the quality of services and health promotion. The aim of this study was to investigate the predictive power of moral intelligence on professional commitment of nurses. Method and Materials: This descriptive-analytical study was carried out on 100 nurses and 300 patients selected by stratified random sampling. Data were collected using the Lenik & Kiel moral Intelligence Questionnaire and Nurse Professional Commitment Questionnaire. Data were analyzed using descriptive analysis and regression. Results: The results showed that there was a significant statistical relationship between moral intelligence and professional commitment (P=0.001). There was a significant relationship between demographic variables, age and work experience with moral intelligence and two variables of gender and professional commitment (P <0.05). In addition, regression showed that dimensions of nurses ‘moral intelligence account for 41% of the variance of nurses’ professional commitment. of the four dimensions of nurses’ moral intelligence, compassion had the most significant effect (P=0.03, ?=0.32). Conclusion: The results of this study showed that moral intelligence is associated with professional commitment and is able to predict it. Therefore, it is recommended that nursing managers and authorities to put the Strengthening nurses’ moral intelligence in the list of their priorities.